Mystic Mythopoiesis of Pre-Islamic Arabic Odes - Urbonaitė, Dalia (Acta Orientalia Vilnensia, 2005)
Institute of Oriental Studies, Warsaw UniversityQaùīdas, the Pre-Islamic Arabic odes, were for years regarded as a model of ideal excellence in Arabic poetry, rhetoric and a way of innermost expression of pure Arabic mind. Poems, made up from several rigorously defined elements, although the definition of poem came up retrospectively, i.e. the clarified form the times of ‘Abbāsid dynasty (750–1258 AD) was imposed on earlier spoken poetry when writing it down, were constructed to specific purposes connected with cyclic tribe-life in desert. Such poetical constructs with repeated motifs from a closed catalogue, which start with a description of an abandoned camp and regret of the parted beloved and end with complaints of the poet’s fate, self-appraisal, shedding tears for fallen tribe members or satire on the enemy tribe, should be read as a cosmological or cosmogonical text. The mythical basement of the Pre-Islamic Arabic odes could be traced when using mythopoiesis, a linguistic expression which interprets the reality according to a mythical basis which is not subdued to the rules of logic analysis and description. While the Western philosophical tradition defines cognition as a line from objective, scientific discourse/logos to immanent, allegoric mythos, the set of motifs in Pre-Islamic Arabic poetry and images is pluralistic, incoherent, not reducible to objective-scientific terms – hence, possible to be described only by means of mythopoiesis, the form of language that corresponds to the imaginary structure of this poetry.